ANATOMICAL AND FUNCTIONAL OUTCOME IN THE MANAGEMENT OF NON-ARTERITIC ANTERIOR ISCHEMIC OPTIC NEUROPATHY - Regar, Evan; Sidik, M. Sidik (Majalah Oftalmologi Indonesia, 2024)
Introduction: Non-arteritic anterior Ischemic optic neuropathy refers to condition in which damage to the anterior optic nerve is presumed to be secondary to ischemia of the anterior part of the optic nerve. This condition is irreversible, and the visual prognosis is generally guarded. To date, there is no definitive high-grade evidence for an effective treatment of NAION. The purpose of this literature review is to assess the results of currently published literatures regarding the management of non-arteritic anterior ischemic optic neuropathy, taking anatomical and functional outcomes into consideration. Methods: A comprehensive literature search was conducted using online databases (PubMed, EBSCO, Clinical Key, and Google Scholar) using relevant search terms. Included studies were selected based on predefined inclusion criteria. Results: Systemic and locally-administered corticosteroid indicated various responses, as well as anti-VEGF, however suggesting no positive effects. Rho-kinase as a vasodilator improved visual acuity in a small study. Erythropoietin and cytidine diphosphocoline (citicoline) suggested visual acuity improvement, while only citicoline improved visual field improvement and prevent further RNFL thinning, in non-randomized controlled studies. Conclusion: No high-quality evidence of intervention has been shown to enhance both anatomical and functional outcome. Many studies were also insufficient to conclude. Further studies are needed, including neuroprotective and novel vasodilator agents.